Rapid microwave fabrication of new nanocomposites based on Tb-Fe-O nanostructures for electrochemical hydrogen storage application. (15th November 2021) - Mehdizadeh, Pourya; Masjedi-Arani, Maryam; Amiri, Omid; Salavati-Niasari, Masoud
Graphical abstract: Highlights: Synthesis of Tb-Fe-O nanocomposites via rapid microwave technique. Investigation of diverse synthesis circumstances on dimension properties of nanostructures. Consideration of electrochemical hydrogen storage capacity of obtained nanostructures. Discharge efficiency of 490 mAh g −1 after 15 cycles for TbFeO3 /Tb3 Fe5 O12 nanocomposites. Abstract: Nano-sized Tb-Fe-O (TFO) structures were fabricated via rapid microwave route using Tb(NO3 )3 ·6H2 O and Fe(NO3 )3 ·9H2 O precursors and verjuice (lemon juice) complexing agent as a surfactant. Verjuice complexing agent including collection of carboxylic acids control nucleation and growth of formed crystals with creation of spatial barrier around the cations, and finally prevent nano-product agglomeration. Changing of parameters in synthesis reaction consisting of surfactant, microwave power and solvent in turn offers a virtuous control over the nanocomposites size and shape which various compositions of pure TbFeO3 nanoparticles, Tb3 Fe5 O12 /TbFeO3 and TbFeO3 /Tb3 Fe5 O12 nanocomposites obtained. The as-prepared Tb-Fe-O nano-products were characterized thorough scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared (FT-IR), UV–Vis, BET and energy dispersive X-ray (EDX) analyses in terms of crystallinity structure, composition, porosity and morphology. Different forms of Tb-Fe-O nanostructures were evaluated for electrochemical hydrogen storage capacity through chronopotentiometry technique in stable current (1 mA). The achieved Tb-Fe-O nanoparticles could be applied as a favorable candidate active material for electrochemical hydrogen storage. Optical, magnetic and reducible characteristics of Tb-Fe-O nanostructures have positive effect on electrochemical hydrogen storage capacity. It was found out that the TbFeO3 /Tb3 Fe5 O12 nanocomposites have the best electrochemical hydrogen storage performance due to oxidation–reduction process of Fe 2+ /Fe 3+ components which can help to charging-discharging process of hydrogen to increase the storage capability to 490 mAh g −1 after 15 cycles.